An Engineered Pathway for Production of Terminally Sialylated N-glycoproteins in the Periplasm of Escherichia coli - Zhu, Jing; Ruan, Yao; Fu, Xin; Zhang, Lichao; Ge, Gaoshun; Wall, J. Gerard; Zou, Teng; Zheng, Yang; Ding, Ning; Hu, Xuejun (Frontiers in Bioengineering and Biotechnology, 2020)
Terminally sialylated N-glycoproteins are of great interest in therapeutic applications. Due to the inability of prokaryotes to carry out this post-translational modification, they are currently predominantly produced in eukaryotic host cells. In this study, we report a synthetic pathway to produce a terminally sialylated N-glycoprotein in the periplasm of E. coli, mimicking the sialylated moiety (Neu5Ac-α-2,6-Gal-β-1,4-GlcNAc-) of human glycans. A sialylated pentasaccharide, Neu5Ac-α-2,6-Gal-β-1,4-GlcNAc-β-1,3-Gal-β-1,3-GlcNAc-, was synthesized through the activity of co-expressed glycosyltransferases LsgCDEF from Haemophilus influenza, Campylobacter jejuni NeuBCA enzymes and Photobacterium leiognathi α-2,6-sialyltransferase in an engineered E. coli strain which produces CMP-Neu5Ac. C. jejuni oligosaccharyltransferase PglB was used to transfer the terminally sialylated glycan onto a glyco-recognition sequence in the tenth type III cell adhesion module of human fibronectin. Sialylation of the target protein was confirmed by lectin blotting and mass spectrometry. This proof-of-concept study demonstrates the successful production of terminally sialylated, homogeneous N-glycoproteins with α-2,6-linkages in the periplasm of E. coli and will facilitate the construction of E. coli strains capable of producing terminally sialylated N-glycoproteins in high yield.